Prospects of cosmopolitan classrooms within a Malaysian university / Jamiah Baba and David Beckett - Baba, Jamiah; Beckett, David (ACRULeT, Faculty of Education & UiTM Press, 2013)
This paper examines lecturers’ practices in adult teaching and learning in University X. We use this analysis to think about better learning for adults in a cosmopolitan world. In our fi eldwork, teaching is viewed as “a complex set of relational exchanges between heterogeneous and differentially positioned human subjects” (Luke, 2004, p. 1429), and how these can be fruitfully accommodated in the classrooms by facilitation of understandings of each others’ circumstances. We show aspects of universality and shared values that Appiah (2006) advocates in his notion of Cosmopolitanism. We claim that in teaching Malaysian adults, lecturers need to recognise and can build upon the cosmopolitan nature of the pedagogical relationships formed within their classrooms.